Effect of Diagnostic Assessment on Basic Education Students’ Achievement in Basic Science in Jalingo Metropolis, Taraba State, Nigeria - B, Shiaki O.; S, Danjuma; Y, Bernard A.; C, Kachalla (Darul Yasin Al Sys, 2024)
The study focused on the effect of diagnostic Assessment on Basic Education students Achievement in Basic Science in Jalingo metropolis, Taraba State, Nigeria. Two objectives guide this present study which are; to examine the problems in the used of Diagnostic Assessment Strategy based on Students’ Achievement in Basic Science and find out the Mean Achievement Scores of Students’ who were assessed using Diagnostic Assessment Strategy and those assessed without the use of Basic Science Students’ in Jalingo metropolis. The study adopted Quasi-experimental design, using pretest and posttest design. The sample consisted of 13 science teachers and 100 students out of which 50 were males and 50 were females. Two instruments were used for the research “Students Achievement test in Basic Science (SATBS) and Teachers’ Diagnostic Assessment Questions (TDAQ) for both teachers and students. The method used for data analysis were mean, standard deviation and t-test distribution. Results revealed that there is no gain in mean achievement of students assessed using DAS. At 5% level of significance, it was shown that there is Significant Difference between the Mean Achievement scores of students assessed using DAS and those without the use of DAS in the selected schools. It was recommended that teachers need to be given training on how to use DAS effectively through providing them with Training programmes that will equipped their understanding of DAS and Also ensure each formative assessment given the classroom should contain DAS in other to allow students get used to the procedure while learning since teachers believe that Students do not find it difficult in expressing their thought.